PENGARUH LITERASI KEUANGAN TERHADAP KINERJA DAN KEBERLANJUTAN UMKM DI KOTA SURABAYA - YANI RAHAYU, APRISTI (Jurnal Ilmu Manajemen (JIM), 2017)
This research aims to investigate the influence of financial literacy toward the performance and sustainability of UMKM in Surabaya. It uses independent and dependent variable for the research. Independent variable is financial literacy which is measured by using financial knowledge with 8 questions. Whereas, dependent variable consist of performance which is measured by 5 questions indicator and the sustainable is measured by using 7 questions. The use sample of this research is 100 respondent of UMKM in Surabaya. Data are collected by using Questionnaire. The technique uses Partial Least Square (PLS). The result of the analysis shows that financial literacy effects the performance and sustainability of UMKM in Surabaya. It means that the higher level of financial literacy, business owners can manage their business performance well and finally the business has long-term sustainability. Key Words: UMKM, Financial Literacy, Performance, Sustainabilit